Analisis Yuridis Pemungutan Pajak Dalam Transaksi E-Commerce di Indonesia - Ni Nyoman Ayu Paramitari; Ida Ayu Putu Widiati; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
The development of the internet in the business world, especially trade, provides many benefits but also provides losses for both sellers and buyers. E-Commerce is an activity to sell and buy goods and / or services through the internet network (Online). The rapid development of E-Commerce in Indonesia raises questions about the taxes imposed on this E-Commerce transaction. The government also began to consider tax regulation that was in accordance with E-Commerce transactions in Indonesia. This research was analyze the scope of E-Commerce transactions in Indonesia and how the tax base applies in E-Commerce transactions in Indonesia. The research method used in this paper is the normative research method, where the author uses literature in accordance with the laws and regulations. The results of the thesis research that I get is the imposition of tax on E-Commerce transactions similar to conventional trade transactions in accordance with the laws and regulations governing the provisions of E-Commerce tax, namely the Director General of Tax Circular Number.SE-62 / PJ / 2013 concerning Affirmation of Taxation Terms For E-Commerce Transactions. Perkembangan internet dalam dunia bisnis khusunya perdagangan, memberikan banyak keuntungan namun juga memberikan kerugian baik bagi penjual maupun pembeli.E-Commerce merupakan kegiatan menjual dan membeli barang dan/ atau jasa melalui jaringan internet (Online). Pesatnya perkembangan E-Commerce di Indonesia menimbulkan pertanyaan mengenai pajak yang dikenakan dalam transaksi E-Commerce ini. Pemerintah juga mulai menimbang mengenai pengaturan pajak yang sesuai dengan transaksi E-Commerce di Indonesia. Penelitian ini menganalisis ruang lingkup transaksi E-Commerce di Indonesia dan bagaimana dasar pengenaan pajak dalam transaksi E-commercedi Indonesia. Metode penelitian dalam penelitian yang digunakan dalam penelitian ini adalah metode penellitian normatif, dengan pendekatan peraturan perundang-undangan. Hasil penelitian menunjukkan bahwapengenaan pajak atas transaksi E-Commerce sama dengan transakssi perdagangan konvensional yang sesuai dengan peraturan perundangan mengatur ketentuan pajak E-Commerce yaitu Surat Edaran Direktur Jenderal Pajak Nomor. SE-62/PJ/2013 Tentang Penegasan Ketentuan Perpajakan Atas Transaksi E-Commerce.